Analisis Kinerja Simpang Tak Bersinyal di Simpang Mengkreng Untuk Perencanaan Jalan Tol Kertosono – Kediri - Cahyono, Muhammad Shofwan Donny; Muhtadi, Adhi; Wibisono, R Endro (Universitas Dr. Soetomo, 2019)
The mengkreng intersection is a very congested route because its location is near Nganjuk, Kediri and Jombang Regencies for the economic distribution of the West and East Java Provinces. Traffic engineering management is needed so that the intersection is not increasingly saturated. As a benchmark, traffic performance forecasting is carried out for 3 years from 2019 to 2022. Based on forecasting results, the Mengkreng intersection will decrease its DS value by carrying out the Kertosono - Kediri toll road development plan so that the DS value is below 1 (one). In 2019 the lowest DS was 0.79, while the highest DS was 1.61. While in 2022 the lowest DS is 0.45, while the highest DS is 2.72. The solution to deal with traffic congestion in 2045 is through traffic engineering and vehicle restrictions.